Ficus macrophylla Desf. ex Pers. Leaves (Moraceae) Possess Antimicrobial Potential for the Prevention of Bacterial Infections: Preliminary In Vitro Study - Truchan, Mariola; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Góralczyk, Anna; Honcharenko, Vitaliy; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The aim of this study was to test the efficacy of ethanolic extract prepared from Ficus macrophylla Desf. Ex Pers. leaves against Gram-positive and Gram-negative bacteria in order to evaluate the possible use of this plant in the prevention of bacterial infections. The testing of the antibacterial activity of the plant extract was carried out in vitro by the Kirby-Bauer disc diffusion technique. Gram-negative bacteria Klebsiella pneumoniae (ATCC 700603), Pseudomonas aeruginosa (ATCC 27853), and Escherichia coli (ATCC 25922), as well as Gram-positive bacteria Staphylococcus aureus (ATCC 25923), methicillin-resistant Staphylococcus aureus (NEQAS 3679) and Streptococcus pneumoniae (ATCC 49619), as well as fungus Candida albicans locally isolated were used as test organisms. Our results revealed that the ethanolic extract of F. macrophylla leaves possessed mild activity against the Gram-positive and Gram-negative bacteria. However, S. pneumoniae and E. coli appeared to be less sensitive to the F. macrophylla extract. Thus, F. macrophylla possesses the medicinal potential for the therapy of bacterial infections induced by S. aureus and may be used as a natural antiseptic and antimicrobial agent in medicine. Moreover, the antibacterial activity of this plant would help for the development of a new alternative medicine system which has no adverse effects. Further investigation is necessary to identify those bioactive compounds, which will be a platform for clinical applications. Finally, we believe that these findings are important in order to evaluate the significance of collections of tropical plants maintained under glasshouse conditions at Botanical Gardens worldwide and to plan the conservation strategy by the establishment of national collections of plants with valuable characteristics with the prospects of their use as sources of antimicrobial agents.